Transitional Pain Care in Quebec: Did We Forget Our Youths? A Brief Research Report - Kudrina, Irina; Bartlett, Gillian; Pagé, M. Gabrielle; Shir, Yoram; Tourian, Leon; Choinière, Manon; Vedel, Isabelle (Frontiers in Pain Research, 2022)
Adolescents and young adults (AYAs) represent a unique population with distinct psycho-social risks and care needs. About 10% of AYAs live with chronic pain and transition to adult pain care between 16 to 25 years of age. These transitions in care happen simultaneously with other bio-psycho-social changes and require flexible multi-disciplinary support models. As it stands, transitional pain care appears sub-optimal, fragmented, and opportunistic in Quebec (Canada). The objective of this Brief Report is therefore, to present our study findings and propose a multi-disciplinary transitional framework vision applicable to AYAs living with chronic pain. Data were collected using a sequential-consensual qualitative design with a longitudinal participatory component. The consecutive stages of this work included an exploratory stage, semi-structured interviews with primary care providers, and inter-disciplinary deliberative stakeholder consultations groups. Deductive inductive thematic approach and the three-level Health Care Transition Research Consortium’s theoretical framework were used to analyze the data. A representative group of stakeholders discussed findings from the first two steps, made fifteen actionable recommendations and formulated their vision of a transitional pain care model that can be further adopted to other settings. The study results present important insights into various psycho-social factors associated with transitional pain care for AYAs.